Oriental splendor [videorecording] - Barrat, James; Iwata, Mary Ellen; Janse, Andre; Kaptijn, Ellen; Okkerse, Tom; Schots, Frank; Schroevers, Martijn; Taylor, David; Verkerk, Mark (Great Palaces of the World, 1995)
A concubine rose to become empress of all China, and squandered her nations destiny on her own private pleasure, at the Summer Palace of Beijing. From India's Red Fort, a Maghul emperor gazed upon the Taj Mahal - a movement to eternal love and a broken heart. At Thailand's Royal Palace of Bangkok, a woman named Anna tutored the future king of Siam, and a love monk held off the armies of Europe. This Asian journey ends at an entire city of Palaces built on the summit of a volcano, India's Jodhpur.